How ancient Europeans saw the world vision, patterns, and the shaping of the mind in prehistoric times - Wells, Peter S. (Princeton Princeton University Press, 2012)
The people who inhabited Europe during the two millennia before the Roman conquests had established urban centers, large-scale production of goods such as pottery and iron tools, a money economy, and more. This title argues the visual world of these late prehistoric communities was different from those of ancient Rome's literate civilization.
Of monsters and flowers -- Seeing and shaping objects -- The visual worlds of early Europe -- Frame, focus, visualization -- Pottery : the visual ecology of the everyday -- Attraction and enchantment : fibulae -- Status and violence : swords and scabbards -- Arranging spaces : objects in graves -- Performances : objects and bodies in motion -- New media in the late iron age : coins and writing -- Changing patterns in objects and in perception -- Contacts, commerce, and the dynamics of new visual patterns -- The visuality of objects, past and present.
Includes bibliographical references (pages 249-280) and index.
Keywords: Prehistoric peoples -- Europe, Western; Material culture -- Europe, Western; Antiquities, Prehistoric -- Europe, Western; Symbolism; Bronze age -- Europe, Western; Iron age -- Europe, Western